UK Consensus on Normal Tissue Dose Constraints for Stereotactic Radiotherapy. Issue 1 (January 2018) - Hanna, G.G.; Murray, L.; Patel, R.; Jain, S.; Aitken, K.L.; Franks, K.N.; van As, N.; Tree, A.; Hatfield, P.; Harrow, S.; McDonald, F.; Ahmed, M.; et al.
Abstract: Six UK studies investigating stereotactic ablative radiotherapy (SABR) are currently open. Many of these involve the treatment of oligometastatic disease at different locations in the body. Members of all the trial management groups collaborated to generate a consensus document on appropriate organ at risk dose constraints. Values from existing but older reviews were updated using data from current studies. It is hoped that this unified approach will facilitate standardised implementation of SABR across the UK and will allow meaningful toxicity comparisons between SABR studies and internationally.